Assessment of Civil Servants’ General Competencies while Implementing the Civil Service Competency Model in Lithuanian Municipalities - Liukinevičienė, Laima; Buivydienė, Lina (Socialiniai tyrimai, 2016)
This paper presents summarized results of a survey on the new Civil Service Competency Model implemented in the Republic of Lithuania. Mažeikiai District Municipality was chosen for this survey.This complex study using qualitative research (semi-structured individual interviews) and quantitativeresearch (questionnaire with closed questions for opinion investigation) methods confirmed scientists’ opinion about the benefits of a centralised assessment of key competencies in the selection process and showed that a general aptitude test should be continuously revised and updated. Municipal authorities emphasised that specific and so far not assessed but very important competencies, such as decision making, project development, managerial, should be assessed. 25 civil servants from MažeikiaiDistrict Municipality, who took part in the competition for a position and passed a general aptitude test, supported centralised assessment of general competencies as contributing to the objectivity and transparency of the selection process.
Keywords: civil service; competence; competency model; general competencies